Compendium of International and National Legal Frameworks on Sexual Harassment in the Workplace - World Bank (World Bank, Washington, DC, 2019)
Sexual Harassment in the Workplace (SHWP) is a universal and widespread phenomenon that affects millions of women of all social strata worldwide. It is an endemic issue that has gained increased visibility and attention since the beginning of the “#MeToo” movement. In this Compendium on International and National Legal Frameworks on Sexual Harassment in the Workplace (the “Compendium”), SHWP is understood as a gender-specific form of violence, commonly directed against women and occurring in employment or the workplace. It includes requests for sexual favors, unwelcome sexual advances or other sexual conduct, whether physical or verbal, which involves a “quid pro quo” aspect (e.g. request for sexual favors used to make employment decisions) and/or creates an intimidating, hostile, toxic, humiliating or offensive working environment. As one of the pervasive expressions of gender-based violence, it reflects discriminatory social norms, stereotypes, impunity and gender inequality. SHWP is viewed as a development challenge and has high economic and social costs. Despite its serious implications for women, employers and society at large, the behavior is widely accepted and minimized. The Compendium provides a survey of the key international and regional instruments as well as national legislation as they relate to SHWP.